Energetic and biochemical valorization of cork boiling wastewater by anaerobic digestion - Gil, Luís (2014)
In addition to energy benefits, anaerobic digestion offers other interesting advantages. The cork industry is of great environmental, economic and social significance in the western Mediterranean region, with Portugal being the world-leading producer and exporter. Cork boiling wastewater (CBW) is a toxic and recalcitrant organic effluent produced by this sector, which constitutes a serious environmental hazard. However, there is no documented research on anaerobic treatment/valorization performed with this effluent. The work presented here was developed with the aim to use the anaerobic digestion process to convert the CBW polluting organic load into an energy carrier gas and valuable molecules for industry.